The vertex separator problem: a polyhedral investigation - Balas, Egon; Souza, Cid C. de (Mathematical programming, 2005)
The vertex separator (VS) problem in a graph G =( V , E ) asks for a partition of V into nonempty subsets A , B , C such that there is no edge between A and B , and | C | is minimized subject to a bound on max{| A |,| B |}. We give a mixed integer programming formulation of the problem and investigate the vertex separator polytope (VSP), the convex hull of incidence vectors of vertex separators. Necessary and sufficient conditions are given for the VSP to be full dimensional. Central to our investigation is the relationship between separators and dominators. Several classes of valid inequalities are investigated, along with the conditions under which they are facet defining for the VSP. Some of our proofs combine in new ways projection with lifting. [PUBLICATION ABSTRACT